Positive time use: a missing link between time perspective, time management, and well-being - Osin, Evgeny; Boniwell, Ilona (Frontiers in Psychology, 2024)
Based on qualitative interviews, we propose a concept of positive time use comprised by four components: self-congruence of daily activities, balance between activities, efficient use of time, and a sense of mastery over one's time. Using data from two UK adult samples (N = 173 and N = 357), we developed a new measure, Positive Time Use Inventory (PTUI). The associations of positive time use with balanced time perspective, affect balance, satisfaction with life, sense of coherence, and self-reported satisfaction with time use indicate convergent and discriminant validity of the new measure. Positive time use partially explained the associations of balanced time perspective with subjective well-being and fully mediated the effects of future time perspective and time management on subjective well-being. We propose positive time use as a new model of temporal well-being, which brings together the notions of work-life balance, time efficiency, and time mastery in a single comprehensive framework, helping to inform the time management coaching interventions.